Static Adsorption of Sr2+ with Low Concentration by Granulated Ca-Alginate - Wang1, Xiaojuan; Wu1, Beilei; Ma3, Chun'an (Asian Journal of Chemistry, 2013)
The adsorption of Sr2+ from solution with low concentration onto dried Ca-alginate was investigated in batch system. The adsorption dynamics, thermodynamics and effects of pH on Sr2+ sorption capacity were carried out and the energy parameters of adsorption were computed. The results show that the adsorption of Sr2+ onto dried Ca-alginate was rapid and low temperature was in favour of adsorption. The adsorption was considered a spontaneous exothermic process. The capacity of adsorption reaches the maximum when pH was 7. The energy parameters and electronic property of system have discovered that the MM block has the best adsorptive effect of Sr2+ in all three kinds of blocks.